Utilization of coal fly ash to enhance the bearing capacity of road base - M. Radwan, Ashraf Abdalla (2023)
Coal is responsible for the generation of around 38 percent of the power that is used throughout the entire planet. In the last two decades, there has been a rise in the number of chances for recycling and usage of fly ash from coal combustion due to its hydrophobic and cementitious properties. However, there is still limited commercialization of coal fly ash (CFA) in road construction. The focus of this research is to determine the bearing capacity of a CFA-treated crusher run used as a road base course. In order to determine the appropriate percentage of CFA, the crusher run was mixed with various percentages of Class F CFA, including 10%, 15%, 20%, and 25%. The proctor Compaction test (PCT), soaked and unsoaked California Bearing Ratio (CBR) tests, and Unconfined Compressive Strength Test (UCST) were then used to evaluate the bearing capacity of the CFA-treated crusher. The result shows that as the percentage of CFA increased, the Optimum Moisture Content (OMC) and Maximum Dry Density (MDD) decreased compared with the control specimen. The soaked and unsoaked CBR of the CFA-treated crusher run with 20% CFA increased by approximately 32% and 26% respectively that of the control specimen. Therefore, it is proven that utilization of CFA up to 20% into crusher run could enhance the bearing capacity of the road base.